Application of the Internet of Things (IoT) based digital platform for â€œPeduli, Keamanan, dan Ketertibanâ€ (PEKERTI) - Fadlika, Irham; Afandi, Arif Nur; Gumilar, Langlang; Andriansyah, Muhammad Rizal; Mistakim, Eka; Fakhri, Achmad Syahrudin; Gunawan, M. Ricko (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
This community service program is implemented in RT 09 RW 06 Penanggungan Village, Klojen District, Malang City. This is a housing estate that is located close to several campuses, making it vulnerable to being a crime target. In this program, we present an idea to solve this problem by creating an Internet of Things (IoT) based Android application â€œPeduli, Keamanan, Ketertiban" (PEKERTI). This system acts as a medium for partner residents to monitor their environmental conditions through installed CCTV cameras, exchange information, and inform each other, to send voice messages to be broadcasted through loudspeakers if there are indications of dangerÂ or crime-prone conditions. This program relies on four main stages, namely analysis and question and answer, preparation of supporting equipment, PEKERTI application design, and evaluation design. The results showed several positive responses from the Penanggungan community who assessed the effectiveness of this activity, marked by increased enthusiasm, order, concern, security, and comfort.